Role and Mechanism of Rhizopus Nigrum Polysaccharide EPS1-1 as Pharmaceutical for Therapy of Hepatocellular Carcinoma - Chu, Guangyu; Miao, Yingying; Huang, Kexin; Song, Han; Liu, Liang (Frontiers in Bioengineering and Biotechnology, 2020)
Objective: This work is to study the effect of Rhizopus nigrum polysaccharide EPS1-1 on hepatocellular carcinoma (HCC) in vitro and in vivo. Methods: HepG2 and Huh-7 cells and nude mice models of liver cancer were used in this study. The cells and nude mice were treated with EPS1-1 at different concentrations. The CCK8 assays were used to measure the proliferation activity of cells, apoptosis was determined with flow cytometry, cell migration was measured by wound-healing assays, cell invasion was evaluated by Transwell assays, and the survival time of different groups of tumor-bearing mice was compared. Real-time PCR and Western blot was used to measure the expressions levels of genes mRNAs and proteins related to proliferation, apoptosis, migration and invasion. Results: In vitro experiments revealed that when treated with EPS1-1, HepG2, and Huh-7 cell proliferation activity decreased, while there was an increase for the apoptosis rate, and the migration and invasion capabilities increased significantly. In vivo experiments showed that EPS1-1 could significantly reduce the tumor growth and lung metastasis of HCC, and prolong the survival of tumor-bearing nude mice, furthermore, EPS1-1 has no apparent damage to heart, liver, and kidney. Further studies showed that EPS1-1 could affect the expression of proliferation-related genes CCND1 and c-Myc, apoptosis-related genes BAX and Bcl-2, migration, and invasion related genes Vimentin and Slug, thereby affecting the biological process of HCC. Conclusion: EPS1-1 can inhibit the malignant process of HCC in vitro and in vivo, which indicates that EPS1-1 has the potential value of clinical application as chemotherapy or adjuvant in the treatment of liver cancer.